2014
DOI: 10.1186/1471-2164-15-643
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of free-living Bradyrhizobium diazoefficiens: highlighting potential determinants of a successful symbiosis

Abstract: BackgroundStrain CPAC 7 (=SEMIA 5080) was recently reclassified into the new species Bradyrhizobium diazoefficiens; due to its outstanding efficiency in fixing nitrogen, it has been used in commercial inoculants for application to crops of soybean [Glycine max (L.) Merr.] in Brazil and other South American countries. Although the efficiency of B. diazoefficiens inoculant strains is well recognized, few data on their protein expression are available.ResultsWe provided a two-dimensional proteomic reference map o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 127 publications
(163 reference statements)
0
16
0
Order By: Relevance
“…Total RNA was extracted using Trizol® reagent (Life Technologies) as previously described [ 66 ]. The total concentrations were estimated in a NanoDrop ND 1000 spectrophotometer (NanoDrop-Technologies, Inc., City etc.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted using Trizol® reagent (Life Technologies) as previously described [ 66 ]. The total concentrations were estimated in a NanoDrop ND 1000 spectrophotometer (NanoDrop-Technologies, Inc., City etc.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted using Trizol® reagent (Invitrogen/Life Technologies) as previously described [ 47 ]. The total RNA concentration was estimated in a NanoDrop ND 1000 spectrophotometer (NanoDrop-Technologies, Inc.) and the integrity was assessed by gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…This interpretation is essential to develop biotechnological approaches for optimizing plant acclimatisation techniques and to enhance the microbial activity of soil for assuagement in crops [ 62 ]. Gomes et al [ 63 ] observed a promotion in the growth of the host due to elevated photosynthetic proteins, transport proteins and chaperones such as GroEL and DnaK during temperature stress, drought and metal toxicity. Recent researches have shown that changes in plant morphology, physiology, transporter action, exudation profiles of roots and vicissitudes might trigger the plant to employ microbes with stress-reducing abilities and potentially enhancing the crop under stress conditions.…”
Section: Plant-microbe Beneficial Interactionmentioning
confidence: 99%